The Effect Long Time Suplementation of Ferrous Sulphate to Blood Glucose Levels In Pregnant Rats - Fadhilah, Siti; Pramestiyani, Mustika (Universitas Islam Lamongan, 2020)
Iron supplements and an increase in reserves of iron in the blood was associated with complications in pregnant women because of an increase in oxidative during stress. The purpose of this research is to knowing blood sugar levels while on pregnant rats (Rattus novergicus) which given ferro sulfate with different length of time. This research was design as an experimental research design as post test only control group design. The sample that used was 24 rats strain wistar which divided into 1 control group (no exposure) and 3 treatment groups (granting of ferro sulfate dosage 60mg/day through the sonde for 20 days, 14 days and 6 days). The analysis of data was using Anova One way test. The result of Kruskal Wallis test on acquired GDS levels got any meaningful differences of average levels of four GDS sample observation group (p-value=0.001). The LSD test results showed there was any meaningful difference of GDS average level between control group (150.67±31.07a) with granting treatment group of ferro sulfate during 20 (P1=215.33±22.9b), 14 days (P2 = 191.50 8.11 ± c) and 6 days (P3 = 155.5 ± 18:59 d). The conclusion of this study is as short as granting time of ferro sulfat can decreased the GDS level in pregnant rats.